Aristotelian Mind and Genesis of G. Hegel’s Principle of Pure Being - Adelšinas, Grigorijus (Problemos, 1990)
The moments forming the principle of pure being are discussed in the paper. The moments are the following: the dialectics of the combination of determinate and indeterminate, the problem of immediate, and the logical sense of the indetermination of pure being. The three moments are related to the characteristics of Aristotelian mind as the principle of ideality and individuality, forming on its turn all the forms and realising all the possible realisations of matter.